2020
DOI: 10.12657/folmal.028.001
|View full text |Cite
|
Sign up to set email alerts
|

Genital morphology differentiates three subspecies of the terrestrial slug Arion ater (Linnæus, 1758) s.l. and reveals a continuum of intermediates with the invasive A. vulgaris Moquin-Tandon, 1855

Abstract: The terrestrial slug Arion vulgaris Moquin-Tandon (= A. lusitanicus auct. non Mabille) is an important agricultural pest that has invaded much of Europe. Previous work has demonstrated hybridisation with A. ater (Linnaeus) s.l. We describe the genital anatomy of morphological intermediates found in eastern Saxony (Germany), comparing them with the parent species. We recommend a standard method of genital dissection and consider a set of five genital characters. The intermediates demonstrate the homology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Very detailed genetic studies using microsatellites also confirmed many cases of hybridisation (Hutchinson et al 2021), although only ca. 4% of the population had anatomies identified as hybrids (Reise et al 2020). Our results based on anatomical identification revealed a small proportion of hybrids (5%), which partly may be due to poor sampling on a few sites; however, genetic data indicate that hybridisation is not rare (Hatteland et al 2015, Zemanova et al 2017.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Very detailed genetic studies using microsatellites also confirmed many cases of hybridisation (Hutchinson et al 2021), although only ca. 4% of the population had anatomies identified as hybrids (Reise et al 2020). Our results based on anatomical identification revealed a small proportion of hybrids (5%), which partly may be due to poor sampling on a few sites; however, genetic data indicate that hybridisation is not rare (Hatteland et al 2015, Zemanova et al 2017.…”
Section: Discussionmentioning
confidence: 56%
“…5). In general, all specimens which did not fit into the pure species were determined as potential hybrids, similar to other studies (Reise et al 2020, Hutchinson et al 2021. It was difficult to decide whether the ligula-bearing part should be called atrium or oviduct for the intermediate forms.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations